2012
DOI: 10.1371/journal.pone.0039413
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of ErbB4 in Breast Cancer

Abstract: ErbB4 is a receptor tyrosine kinase that can signal by a mechanism involving proteolytic release of intracellular and extracellular receptor fragments. Proteolysis-dependent signaling of ErbB4 has been proposed to be enhanced in breast cancer, mainly based on immunohistochemical localization of intracellular epitopes in the nuclei. To more directly address the processing of ErbB4 in vivo, an ELISA was developed to quantify cleaved ErbB4 ectodomain from serum samples. Analysis of 238 breast cancer patients demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Four different HER4 mRNA spliced isoforms known as JM-a/CYT1, JM-a/CYT2, JM-b/CYT1 and JM-b/CYT2 have been reported, which are derived from the alternative HER4 mRNA splicing [30, 50, 51]. In contrast to JM-b variant, the JM-a region consists of Adam-17 (TACE) cleavage site that allows initial process of HER4 proteolytic cleavage to produce the extracellular domain (ECD) and intracellular domain (ICD) [25, 29, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Four different HER4 mRNA spliced isoforms known as JM-a/CYT1, JM-a/CYT2, JM-b/CYT1 and JM-b/CYT2 have been reported, which are derived from the alternative HER4 mRNA splicing [30, 50, 51]. In contrast to JM-b variant, the JM-a region consists of Adam-17 (TACE) cleavage site that allows initial process of HER4 proteolytic cleavage to produce the extracellular domain (ECD) and intracellular domain (ICD) [25, 29, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis results in generation of an intracellular domain fragment that has functions distinct from that of the intact receptor. Nuclear HER4 has been detected in several cancer types, including medulloblastoma and breast cancer, and shed HER4 ectodomain has been detected in serum from breast cancer patients [14]. In preclinical models, inhibition of HER4 proteolysis with a blocking antibody represses xenograft tumor growth in mice [14].…”
Section: Her Biology and Role In Cancermentioning
confidence: 99%
“…Nuclear HER4 has been detected in several cancer types, including medulloblastoma and breast cancer, and shed HER4 ectodomain has been detected in serum from breast cancer patients [14]. In preclinical models, inhibition of HER4 proteolysis with a blocking antibody represses xenograft tumor growth in mice [14]. However, the importance of HER4 intracellular/ectodomain fragments as prognostic markers and drivers of disease remain poorly defined.…”
Section: Her Biology and Role In Cancermentioning
confidence: 99%
“…Despite of the controversial aspect of association between ErbB4 expression signature and clinical outcomes including the survival of breast cancer patients [5e9, 33], mice xenograft along with in vitro studies have proposed an oncogenic role for ErbB4 protein in breast cancer [10,34,35]. A number of population-based GWAS studies have demonstrated that germ-line ErbB4 variations are associated with breast cancer risk, including rs13393577, rs905883, rs7564590, rs7558615.…”
Section: Discussionmentioning
confidence: 99%